MICE AND THE FUTURE OF TOURISM IN INDONESIA - Resti Hardini; Rahayu Lestari; Kumba Digdowiseiso; Nguyen Duc Tri (RADJA PUBLIKA, 2024)
The impact of the MICE (Meetings, Incentives, Conferences, and Exhibitions) industry on the Indonesian tourism sector is a noteworthy aspect that warrants particular consideration. More precisely, the MICE industry exerts a substantial and favorable influence on the expansion of tourism in Indonesia. This research aims to investigate the impact of the MICE industry on the growth of the tourism sector in Indonesia. It seeks to determine the extent to which this industry contributes to the increase in tourist visits and national income. Additionally, the study aims to identify the factors that influence the development of the MICE industry in Indonesia, including government policy, infrastructure readiness, and the active participation of industry players. Qualitative research methods are a suitable and appropriate option. The findings of this investigation are as follows: Developing high-quality MICE infrastructure and consistently monitoring global trends will be crucial in shaping the future of tourism in Indonesia. Indonesia's ascent to becoming a highly sought-after MICE destination on the global stage will be achieved through the consistent adoption of technology, improved infrastructure readiness, and effective support from the government in creating a favorable environment.